Let's Play Dead - Connolly, Sheila (Connolly, Sheila. Museum mysteries., 2011)
"When Nell is invited to the beloved Philadelphia children's museum, 'Let's Play', for a sneak preview of a newly installed exhibit based on the Harriet the Hedgehog book series, she's in for quite a shock. In the middle of her visit, one of the installers get a severe jolt from working on an electronically animated forest creature. He recovers, but when a second man gets zapped--this time fatally--it sparks a homicide investigation, with Nell right in the middle of things. Is someone out to sabotage the exhibition, or to discredit the museum president, Arabella Heffernan? Even with the help of her potential beau, FBI Special Agent James Morrison, it's ultimately up to Nell to channel her energy into finding the killer--before she gets burned herself ..."--Page 4 of cover.